2022
DOI: 10.1002/ejoc.202200193
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heterocyclic‐Fused Furans and Dihydrofurans via (4+1)‐Annulation with Ylide: Exploration of Unique Reactivity Behavior of α‐Carbonyl Sulfoxonium Ylide

Abstract: A (4 + 1)-annulation of arylidene heterocyclic-N-fused imidazolones with α-carbonyl sulfoxonium ylides has been developed. The reaction enabled efficient access to a range of N-heterocycle-fused furans, such as secondary hydroxyl and the structural parts of drug/bioactive compounds. A unique triplerole of α-carbonyl sulfoxonium ylides and a characteristic stereo-electronic functional behavior of the arylidene N-fused imidazolones have been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Very recently, Guchhait et al reported a divergent synthesis of fused dihydrofurans 18 and furans 19 via the [4 + 1]-annulation of arylidene-benzimidazolones 17 with keto-stabilized ylides 4. 19 In MeCN at 70 °C, the expected formation of dihydrofurans 18 (mixtures of diastereomers) took place. At a higher temperature in DMF, fused furan derivatives 19 were formed as a result of tautomerization and subsequent migration of the double bond (Scheme 8).…”
Section: [4 + 1]-annulations With Sulfur Ylidesmentioning
confidence: 98%
“…Very recently, Guchhait et al reported a divergent synthesis of fused dihydrofurans 18 and furans 19 via the [4 + 1]-annulation of arylidene-benzimidazolones 17 with keto-stabilized ylides 4. 19 In MeCN at 70 °C, the expected formation of dihydrofurans 18 (mixtures of diastereomers) took place. At a higher temperature in DMF, fused furan derivatives 19 were formed as a result of tautomerization and subsequent migration of the double bond (Scheme 8).…”
Section: [4 + 1]-annulations With Sulfur Ylidesmentioning
confidence: 98%
“…The [4 + 1]-annulation of sulfoxonium ylides (Corey ylides) with a variety of Michael acceptors (1,3-conjugated systems) has been well explored. 9 Notably, MacMillan ingeniously achieved highly enantioselective organocatalytic cyclopropanation of R,β-unsaturated aldehydes with stabilized sulfonium ylides based on iminium catalysis and directed electrostatic activation by the use of 2-carboxylic acid dihydroindole as the catalyst (Scheme 1a). 10 However, to the best of our knowledge, there were only two examples of the use of sulfoxonium ylides in the synthesis of cyclopropanes.…”
Section: Introductionmentioning
confidence: 99%